Hemangioma Kavernosa di Kelopak Mata Bawah : Kasus Yang Tidak Biasa - Raudatul Janah; Isti Komah Noor (Jurnal Ilmu Kedokteran, 2024)
Approximately 6-9% of all orbital tumors are orbital cavernous hemangiomas, which are the most prevalent kind of orbital lesion. A case of a 34-years-old male presented with a painless and palpable mass in the lower eyelid, left eye (LE) since three years ago. There was a bluish discoloration of the tarsal conjunctiva of the lower eyelid. The patient underwent resection of the tumor mass, the histopathological results of cavernous hemangioma. Cavernous hemangioma may present in the lower eyelid, which is an uncommon location. Most cavernous reported several cases of cavernous hemangioma in the upper eyelid. But only one case was reported in the lower eyelid, so it is important to keep in mind the differential diagnosis of other eyelid tumors.